2012
DOI: 10.5897/ajpp12.901
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, pharmacology and medicinal properties of Coriandrum sativum L.

Abstract: Coriandrum sativum L. commonly known as "Coriander" is an annual herb, indicated for a number of medical properties in traditional medicine. For a long time, C. sativum has been used in traditional medicines as an anti-inflammatory, analgesic, and antibacterial agent. Its essential oil is also used as a natural fragrance with some medicinal properties. C. sativum has recently been shown to have antioxidant, antidiabetic, hepatoprotective, antibacterial, and antifungal activities. Volatile components, flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 34 publications
0
40
1
8
Order By: Relevance
“…It is very important to underline that the use of plants and other botanical preparations are used, since ancient times, by primitive societies, due to healing properties and therapeutic and psychotherapeutic benefits. It is important to address the fact that plants are widely used to obtain a large variety of drugs, being used in folk medicine for a long time [26][27][28][29][32][33][34][35]. Concerning that plants represent an economic, easily and which are accessible for all of people, they can be used into a variety of diseases, constituting an excellent source of biomolecules able to act like natural antifungal agents and, at the same time, to encourage the search for other alternative treatments.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…It is very important to underline that the use of plants and other botanical preparations are used, since ancient times, by primitive societies, due to healing properties and therapeutic and psychotherapeutic benefits. It is important to address the fact that plants are widely used to obtain a large variety of drugs, being used in folk medicine for a long time [26][27][28][29][32][33][34][35]. Concerning that plants represent an economic, easily and which are accessible for all of people, they can be used into a variety of diseases, constituting an excellent source of biomolecules able to act like natural antifungal agents and, at the same time, to encourage the search for other alternative treatments.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Future studies will be necessary to expand the existing, limited therapeutic drugs for the vast majority of liver diseases. Reports of medicinal plants for the treatment of liver disease are numerous; however, due to space limitations, we will focus on only a few (Ansari et al, 2011;Asgarpanah & Kazemivash, 2012;Asuku et al, 2012;Avila et al, 2011;Ghosh et al, 2011;Gutierrez et al, 2013;Haddad et al, 2011;Ho et al, 2012;Lee et al, 2012;Mihailovic et al, 2013;Nagalekshmi et al, 2011;Nithianantham et al, 2011;Paul et al, 2013;Shivananjappa et al, 2013;Singab et al, 2010;Mukherjee et al, 2009;Rana et al, 2011;Subramanian et al, 2012;Torres-Gonalez et al, 2011;Upadhyay et al, 2013;Xavier et al, 2012;Zhang et al, 2012).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants mentioning
confidence: 99%
“…Various polyphenol and flavonoid compounds, including glycitin, caffeic acid, protocatechuic acid, apigenin, Aliphatic (2E)-alkenals, and alkanals were reported in the aerial parts of C. sativum (21-23) whereas, Quercetin 3-glucuronide, isoquercitrin, and rutin were found in the fruit (24). Recently, several novel phytochemical and pharmacological studies have been performed on C. sativum and results have been reported in review articles (20,25). However, studies have always focused on the roots and aerial parts of C. sativum for their antioxidant properties (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, all parts of the plant are used to alleviate gastrointestinal complaints, bronchitis, muscular spasm, gout, and rheumatoid disorders (16). Several studies performed on this herb reported that the plant has various therapeutic properties, including, anti-microbial, anti-hyperlipidemia, hepato-protective, anti-peroxidative, insulin-releasing, and insulin-like activity (17)(18)(19)(20). Various polyphenol and flavonoid compounds, including glycitin, caffeic acid, protocatechuic acid, apigenin, Aliphatic (2E)-alkenals, and alkanals were reported in the aerial parts of C. sativum (21-23) whereas, Quercetin 3-glucuronide, isoquercitrin, and rutin were found in the fruit (24).…”
Section: Introductionmentioning
confidence: 99%